2015
DOI: 10.1155/2015/537368
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Problem in River Kabul: Accumulation Estimates of Heavy Metals in Native Fish Species

Abstract: The contamination of aquatic systems with heavy metals is affecting the fish population and hence results in a decline of productivity rate. River Kabul is a transcountry river originating at Paghman province in Afghanistan and inters in Khyber Pakhtunkhwa province of Pakistan and it is the major source of irrigation and more than 54 fish species have been reported in the river. Present study aimed at the estimation of heavy metals load in the fish living in River Kabul. Heavy metals including chromium, nickel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
2
7
4
Order By: Relevance
“…Chromium is a vital chemical element that plays an important role in glucose, fat, and protein metabolism ( Mertz, 1993 ). The Cr values from this study were lower than those reported by Ahmad et al (2015) in fish species from the Kabul River, Pakistan (489–703 μg/) and higher than those recorded by Sankar et al (2006) in Calicut, India (0.47 μg/g); Raja et al (2009) in Parangipetti waters, India (0.65–0.92 μg/g); Yilmaz (2003) in Iskenderun Bay, Turkey (1.03–1.79 μg/g); Ahmed and Naim (2008) in the Gulf of Aquba, Red Sea (1.0–10.3 μg/g); Rahman et al (2012) in the Bangshi River, Bangladesh (0.47–2.07 mg/kg); Türkmen et al, 2005 in the northeast of Mediterranean Sea, Turkey (0.07–6.64 mg/kg); and Demirezen and Uruç (2006) in Kayseri, Turkey (8.44–9.51 μg/g). The United States Food and Drug Administration (USFDA) set a maximum permissible Cr content of 12–13 mg/kg for fishes ( USFDA, 1993 ).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Chromium is a vital chemical element that plays an important role in glucose, fat, and protein metabolism ( Mertz, 1993 ). The Cr values from this study were lower than those reported by Ahmad et al (2015) in fish species from the Kabul River, Pakistan (489–703 μg/) and higher than those recorded by Sankar et al (2006) in Calicut, India (0.47 μg/g); Raja et al (2009) in Parangipetti waters, India (0.65–0.92 μg/g); Yilmaz (2003) in Iskenderun Bay, Turkey (1.03–1.79 μg/g); Ahmed and Naim (2008) in the Gulf of Aquba, Red Sea (1.0–10.3 μg/g); Rahman et al (2012) in the Bangshi River, Bangladesh (0.47–2.07 mg/kg); Türkmen et al, 2005 in the northeast of Mediterranean Sea, Turkey (0.07–6.64 mg/kg); and Demirezen and Uruç (2006) in Kayseri, Turkey (8.44–9.51 μg/g). The United States Food and Drug Administration (USFDA) set a maximum permissible Cr content of 12–13 mg/kg for fishes ( USFDA, 1993 ).…”
Section: Discussioncontrasting
confidence: 90%
“…Nickel is an environmental factor that occurs at a very low level and can cause severe pulmonary health problems, such as lung cancer, fibrosis, emphysma, tumors and kidney diseases ( Forti et al, 2011 ). In this review, Nickel values in this study were lower than those reported by Ahmad et al (2015) (75–135 μg/g) in the Kabul River, Pakistan and higher than those reported by Turkmen et al (2005) in Iskenderun Bay, Turkey (0.11–12.9 μg/g); Tuzen (2003) in the Black Sea, Turkey (1.14–3.60 μg/g); Uluozlu et al (2007) in the Black and Aegean seas, Turkey (1.92–5.68 μg/g); and Leung et al (2014) in the Peral River Delta, China (0.44–9.75 μg/g). The Western Australian Food and Drug Regulations set the permissible level of Ni to 5.5 mg/kg wet weight ( Plaskett and Potter, 1979 ).…”
Section: Discussioncontrasting
confidence: 68%
“…Among these sites the last two are more important, as these are being used as dumping site since very long for the discharge of wastes from vegetable, crockery and general markets of Timergara, the major city of the district. The concentration of heavy metals in the present study is much lower than those conducted in other parts of the Khyber Pakhtunkhwa province [16][17][18]. It might be due to the higher anthropogenic activities resulting in dumping and input of heavy industrial effluents and pollutants, domestic sewages and agricultural run offs into those rivers.…”
Section: Discussioncontrasting
confidence: 70%
“…On account of its economic worth and public health value, research regarding heavy metal contents in fish tissues has been carried out in different parts of the world as well as Pakistan [12][13][14][15]. Studies conducted on river Kabul revealed the presence of heavy metals in different fish species including Tor putitora, Ompok bimaculatus, Aorichthys seenghala, Cyprinus carpio, Labeo dyocheilus and Wallago attu in a higher concentration than the permissible limits [16][17][18]. Many recent studies reports the presence of heavy metals in various fish species from different parts of the country [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Water quality of Kabul River has also been deteriorated due to lack of wastewater treatment facility. It receives about 1 m 3 /sec of industrial effluents directly without prior treatment [15][16][17][18][19] . Pakistan and Afghanistan both share water resources of Kabul River and any reduction in flow will have drastic impact on water quality of river.…”
Section: Introductionmentioning
confidence: 99%